Berkeley Castle Tales - Prior, Stuart J.; Horton, Mark; Trimmis, Konstantinos (2023)
Berkeley Castle Tales presents the outcomes of the 15-year-long University of Bristol excavations and landscape research at the Berkeley Castle estate in South Gloucestershire. The project, which in 2016 won the prestigious Current Archaeology award for the Archaeology Project of the Year, aimed at writing, through material culture and extensive archival and geophysical research, the narrative behind the construction of Berkeley Castle, the corresponding town, and the area of the Severn valley that overlooks the borders with Wales. By combining the results of archaeological fieldwork with information contained in the castle's impressive collection of 20,000 historical documents, the project adds greatly to our knowledge and understanding of the early medieval period and the subsequent changes in landscape and society that occurred with the coming of the Normans, with the erection of a castle on the former minster site. Throughout the publication the advances that the Berkeley Castle project offered to archaeological practice, to excavation and geophysics methodology, and to the community and public archaeology are evident, since the editors intend the volume to be a milestone not only for the study of a castle landscape but also for archaeological method and practice.